PENDIDIKAN ISLAM DI MADRASAH: PELUANG PENDIDIKAN INTEGRATIF - TAMRIN (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
Madrasahs as part of the Islamic world's education cannot be denied, including in Indonesia. By taking a different path from school education, madrasahs offer education that is integrated with Islamic values. However, in reality, many madrasahs still have difficulties in developing themselves and have limited access to the use of technology. Therefore, this study aims to explore the opportunities for integrative education in madrasas. With descriptive-analytic qualitative research. This study found that madrasahs have contributed greatly to the development of education in Indonesia. Along with the rapid changes of the times, madrasah functions as a fortress that maintains the moral values and character of the nation, by providing integrated education between scientific aspects and religious teachings. Therefore, in order for the integrative education offered by madrasas to run effectively, it is important to utilize developments in accordance with the times in order to become an opportunity.